2003
DOI: 10.1046/j.1523-1755.2003.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

A complete mutation screen of PKHD1 in autosomal-recessive polycystic kidney disease (ARPKD) pedigrees

Abstract: DHPLC has been established as a rapid mutation screening method for ARPKD. The mutation detection rate was high in severely affected patients (85%), lower in those with moderate ARPKD (41.9%), and low, but significant, in adults with congenital hepatic fibrosis/Caroli's disease (32.1%). The prospects for gene-based diagnostics are complicated by the large gene size, marked allelic heterogeneity, and clinical diversity of the ARPKD phenotype. Identification of some common mutations, especially in specific popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
86
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 31 publications
9
86
2
Order By: Relevance
“…Mutation analyses of ARPKD patients included individuals with predominant liver disease manifest as congenital hepatic fibrosis or Caroli's disease and only mild renal involvement. 6,7,10,[12][13][14]40 In such families, the mutations invariably include at least one predicted amino acid substitution that may act in a hypomorphic manner. In the case of the Pkhd1 del4 mouse model, the transcript bears a deletion of 66 amino acids that includes part of exon 4 and all of exon 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation analyses of ARPKD patients included individuals with predominant liver disease manifest as congenital hepatic fibrosis or Caroli's disease and only mild renal involvement. 6,7,10,[12][13][14]40 In such families, the mutations invariably include at least one predicted amino acid substitution that may act in a hypomorphic manner. In the case of the Pkhd1 del4 mouse model, the transcript bears a deletion of 66 amino acids that includes part of exon 4 and all of exon 5.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the mutations in the genes may also affect the severity of the disease, hence the clinical lesion in mice, and this is borne out in human studies in which genotype-phenotype interactions have been reported. [11][12][13][14] Human mutations in the region of the Pkhd1 del4 mutation have resulted in severe loss of function. For example, one mutation, IVS5 ϩ 1G3 T, predicted to result in loss of the exon 5 splice donor site causing aberrant splicing of exon 5 was found in a child with the severe perinatal lethal presentation associated with presumed complete loss-of-function alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 We therefore recommend that neonatal patients and children with congenital hepatic fibrosis and CaroliЈs disease should be screened for PKHD1 mutations even in the absence of renal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…To date, .700 different PKHD1 mutations are known (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The longest open reading frame of PKHD1 comprises 66 exons and encodes a single-transmembrane protein, called polyductin/fibrocystin, which is mainly expressed in the kidney and liver/cholangiocytes (6,7,19).…”
Section: Introductionmentioning
confidence: 99%